2017
DOI: 10.1016/j.neuroscience.2017.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of pain circuitry in early post-natal development using manganese-enhanced MRI in rats

Abstract: Premature or ill full-term infants are subject to a number of noxious procedures as part of their necessary medical care. Although we know that human infants show neural changes in response to such procedures, we know little of the sensory or affective brain circuitry activated by pain. In rodent models, the focus has been on spinal cord and, more recently, midbrain and medulla. The present study assesses activation of brain circuits using manganese-enhanced magnetic resonance imaging (MEMRI). Uptake of mangan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…In conclusion, the moderate regional-specific correlations of MEMRI signal and pain behaviour reported herein indicate that in vivo MEMRI at 7 T is sensitive to cumulative neural effects of pain behaviour in awake freely moving animals. Further improvements to MEMRI will arise from recent and ongoing refinement of safe manganese doses ( Gálosi et al, 2017 , Poole et al, 2017 ), as well as the use of post-mortem scanning (enabling a longer scan time and therefore resolution) where experimental paradigms allow ( Sperry et al, 2017 ). These developments, combined with an increase of signal to noise ratios through use of optimised acquisition hardware (field strength, dedicated coils), may improve the sensitivity of MEMRI to strengthen future investigations into the neural mechanisms underpinning spontaneous pain in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the moderate regional-specific correlations of MEMRI signal and pain behaviour reported herein indicate that in vivo MEMRI at 7 T is sensitive to cumulative neural effects of pain behaviour in awake freely moving animals. Further improvements to MEMRI will arise from recent and ongoing refinement of safe manganese doses ( Gálosi et al, 2017 , Poole et al, 2017 ), as well as the use of post-mortem scanning (enabling a longer scan time and therefore resolution) where experimental paradigms allow ( Sperry et al, 2017 ). These developments, combined with an increase of signal to noise ratios through use of optimised acquisition hardware (field strength, dedicated coils), may improve the sensitivity of MEMRI to strengthen future investigations into the neural mechanisms underpinning spontaneous pain in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Pain-induced activation in each of these areas was attenuated by pretreatment with morphine. Recently, Sperry et al (2017) performed similar imaging in perfused brains, allowing much longer scan times to improve resolution.…”
Section: Memri In Cns Imagingmentioning
confidence: 99%
“…Since Yang et al (2011) first used MEMRI to map pain circuits, the technique has been used in several studies of pain. MEMRI has proved effective for studying irritant injection (Devonshire et al, 2017; Sperry et al, 2017), nerve injury (Behera et al, 2013; Jeong and Kang, 2018) and thermal (Lei et al, 2014) models of pain. Interestingly, in an investigation into the difference between processing of neuropathic pain and pathological itching using MEMRI, Jeong et al (2016) found differences in processing for each stimulus in the limbic systems.…”
Section: Memri In Cns Imagingmentioning
confidence: 99%
“…Although MEMRI allows for imaging in vivo, a drawback of MEMRI relative to optical imaging is less resolution due to low signal to noise ratio. MEMRI resolution can be increased with longer imaging times readily performed in fixed brains 46 , although fixation precludes longitudinal studies. In living mice imaging longer than 2 hours requires extensive life support inside the scanner bore, technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In rat, MEMRI signal has been correlated with electrophysiology 39 , and with intermediate early gene expression 44 . MEMRI has been applied to understand patterns of neural activity in songbird vocalization 45 ; in neonatal mice for pain response 46 and in rats for barrel whisker stimulation 47,48 and for predator odor response 49 . In Aplysia, the sea slug, Mn 2+ accumulation is proportional to excitatory neural activity measured by electrophysiology 50,51 .…”
Section: Introductionmentioning
confidence: 99%